Methanethiol and Dimethylsulfide Cycling in Stiffkey Saltmarsh - Carrión, Ornella; Pratscher, Jennifer; Richa, Kumari; Rostant, Wayne G.; Farhan Ul Haque, Muhammad; Murrell, J. Colin; Todd, Jonathan D. (Frontiers in Microbiology, 2019)
Methanethiol (MeSH) and dimethylsulfide (DMS) are volatile organic sulfur compounds (VOSCs) with important roles in sulfur cycling, signalling and atmospheric chemistry. DMS can be produced from MeSH through a reaction mediated by the methyltransferase MddA. The mddA gene is present in terrestrial and marine metagenomes, being most abundant in soil environments. The substrate for MddA, MeSH, can also be oxidised by bacteria with the MeSH oxidase (MTO) enzyme, encoded by the mtoX gene, found in marine, freshwater and soil metagenomes. The methanethiol-dependent DMS production (Mdd) pathway has been shown to function in soil and marine sediments, but it has not been characterised in detail in the latter environments. In addition, few molecular studies have been conducted on environmental MeSH consumption. Here, we performed process measurements to confirm that the Mdd-dependent and Mdd-independent MeSH consumption pathways are active in tested surface saltmarsh sediment when MeSH is available. We noted that appreciable natural Mdd-independent MeSH and DMS consumption processes masked Mdd activity. 16S rRNA gene amplicon sequencing and metagenomics data showed that Methylophaga, a bacterial genus known to catabolise DMS and MeSH, was enriched by the presence of MeSH. Moreover, some bacteria isolated from this marine environment lacked known DMS and MeSH cycling genes and can be used as model organisms to potentially identify novel genes involved in MeSH and DMS metabolism. Thus, we are likely vastly underestimating the abundance of MeSH and DMS degraders in these marine sediment environments. The future discovery and characterisation of novel enzymes involved in MeSH and/or DMS cycling is essential to better assess the role and contribution of microbes in global organosulfur cycling.